2012
DOI: 10.1038/tp.2012.8
|View full text |Cite
|
Sign up to set email alerts
|

Association of depressive disorders, depression characteristics and antidepressant medication with inflammation

Abstract: Growing evidence suggests that immune dysregulation may be involved in depressive disorders, but the exact nature of this association is still unknown and may be restricted to specific subgroups. This study examines the association between depressive disorders, depression characteristics and antidepressant medication with inflammation in a large cohort of controls and depressed persons, taking possible sex differences and important confounding factors into account. Persons (18–65 years) with a current (N=1132)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
184
4
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(214 citation statements)
references
References 52 publications
21
184
4
5
Order By: Relevance
“…Although some studies have demonstrated that antidepressants decrease inflammatory cytokines (38,39), others report either no effect (31,40,41) or even increased levels (42,43). This discrepancy is likely due to a number of factors, including the class of antidepressant used for treatment or the heterogeneity of the patient population (44). In our studies, we only included treatment-resistant patients that typically exhibit greater proinflammatory profiles (45), which may contribute to decreased treatment efficacy and increased relapse.…”
Section: Significancementioning
confidence: 99%
“…Although some studies have demonstrated that antidepressants decrease inflammatory cytokines (38,39), others report either no effect (31,40,41) or even increased levels (42,43). This discrepancy is likely due to a number of factors, including the class of antidepressant used for treatment or the heterogeneity of the patient population (44). In our studies, we only included treatment-resistant patients that typically exhibit greater proinflammatory profiles (45), which may contribute to decreased treatment efficacy and increased relapse.…”
Section: Significancementioning
confidence: 99%
“…In a recent metaanalysis on longitudinal studies by Valkanova et al (2013) it was also established that raised CRP levels were associated with an increased risk of subsequent depression. However, these findings are not uniform and in subgroup analyses, elevated CRP was associated with atypical depression (Hickman et al, 2013), somatic symptoms (Duivis et al, 2013), depressed men with an older age of depression onset (Vogelzangs et al, 2012), depressed men in general (Elovainio et al, 2009, Ford and Erlinger, 2004, Liukkonen et al, 2011, depressed patients with a greater history of childhood adversity (Miller and Cole, 2012), and cumulative depressive episodes (Copeland et al, 2012).…”
Section: Inflammation and Immune Response Biomarkersmentioning
confidence: 93%
“…Additionally, rise of inflammatory markers such as CRP, IL-6, and TNF-α, have been reported in a cross-sectional study assessing 2415 participants [26]. Maes et al have accomplished a cross-sectional survey showing a positive correlation between levels of inflammatory markers (TNF-α and IL-1) and the extent of depressive episodes [27].…”
Section: Inflammatory State and Depressionmentioning
confidence: 99%